Valorization of spent coffee grounds recycling as a potential alternative fuel resource in Turkey: An experimental study. (4th March 2018) - Atabani, A.E.; Mercimek, S.M.; Arvindnarayan, Sundaram; Shobana, Sutha; Kumar, Gopalakrishnan; Cadir, Mehmet; Al-Muhatseb, Ala'a H.
ABSTRACT: In this study, recycling of spent coffee grounds (SCG) as a potential feedstock for alternative fuel production and compounds of added value in Turkey was assessed. The average oil content was found (≈ 13% w/w ). All samples (before and after extraction) were tested for scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD), calorific value, surface analysis and porosity, Fourier transform infrared (FT-IR), and elemental analysis to assess their potential towards fuel properties. Elemental analysis indicated that carbon represents the highest percentages (49.59% and 46.42%, respectively), followed by nitrogen (16.7% and 15.5%), hydrogen (6.74% and 6.04%), and sulfur (0.851% and 0.561%). These results indicate that SCG can be utilized as compost, as it is rich in nitrogen. Properties of the extracted oil were examined, followed by biodiesel production. The quality of biodiesel was compared with American Society for Testing and Materials (ASTM) D6751 standards, and all the properties complied with standard specifications. The fatty acid compositions were analyzed by gas chromatography. It was observed that coffee waste methyl ester (CWME) is mainly composed of palmitic (35.8%) and arachidic (44.6%) acids, which are saturated fatty acids. The low degree of unsaturation provides an excellent oxidation stability (10.4 hr). CWME has also excellent cetane number, higher heating value, and iodine value with poor cold flow properties. The studies also investigated blending of biodiesel with Euro diesel and butanol. Following this, a remarkable improvement in cloud and pour points of biodiesel was obtained. Spent coffee grounds after oil extraction is an ideal material for garden fertilizer, feedstock for ethanol, biogas production, and as fuel pellets. The outcome of such research work produces valuable insights on the recycling importance of SCG in Turkey. Implications : Coffee is a huge industry, and coffee has been widely used due to its refreshing properties. This industry generates large quantities of waste. Therefore, recycling of spent coffee grounds for producing alternative fuels and compounds of added value is crucial. Elemental analysis indicated that coffee waste can be utilized as compost, as it is rich in nitrogen. Coffee waste after oil extraction is an ideal feedstock for ethanol and biogas production, garden fertilizer, and as fuel pellets. The low degree of unsaturation provides excellent oxidation stability. Its biodiesel has also excellent cetane number, higher heating value, and lower iodine value.